TANGGAPAN WISATAWAN TERHADAP DAYA TARIK WISATA ALAM TAMAN HUTAN RAYA SULTAN SYARIF HASYIM KABUPATEN SIAK - Suqron, Aufa; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the Tourist Response to the natural tourist attraction of the Sultan Syarif Hasyim Forest Park in Siak Regency. This research uses descriptive quantitative research method. There are 70 samples taken and determined by the researchers themselves based on Masri Singarimbun's Theory. Data collection techniques in this study used Observation, questionnaires and documentation. Likert scale is used to measure intervals in quantitative data. This research uses Marpaung's Theory. The results of the study showed that the Tourist Response to the Natural Tourist Attraction of Sultan Syarif Hasyim Forest Park in Siak Regency was very good. Â Keywords: Tourist Responses, Nature AttractionsÂ